India's Tourism Industry : A study on India's Tourism Demand and the Relationship Between India's Tourism and Economic Growth - Qasmi, Yusra (2013)
The aim of this research is to establish the short run and long run relationships between international tourist arrivals in India, relative price or tourism price and cost of travelling and income and currency exchange rates for the period covering 1981-2009 using cointegration techniques and error correction models. The use of cointegration technique known as the bounds testing approach, developed within the autoregressive distributed lag (ARDL) framework has been used to estimate the model. The main advantage of this approach is that apart from providing robust results in small sample sizes, it needs no a priori knowledge about the integration properties of the variables. The issue of stationarity is investigated through Augmented Dickey-Fuller (ADF) and the Phillip Peron (PP) tests for unit roots. The research also examines the long run and short run dynamics between tourism and economic growth in India using the bounds test developed by Persaran et al. (2001). Phillips and Peron unit root test (1988) and Kwiatkowski et al. (1992) test for unit root have been employed to check for stationarity. And Granger causality test is used for determining the direction of causality.